STUDY ON EMISSIONS OF CARBON DIOXIDE FROM GRAZED PASTURE LAND USING CATTLE URINE - B. Thulasamma; Ch. Harikrishna; A. Saratchandra; P. Amareswari; D.B.V. Ramana (Indian Journal of Veterinary and Animal Sciences Research, 2025)
An experiment was conducted to assess the effect of application of cattle urine at a rate of 0.7 l/m2 area on carbon dioxide (CO) emissions under low, medium and high pasture cover blocks of the grazing area during rainy season at Hyderabad. CO2 emissions was significantly (P